Aggressive and investigative behaviors of two sympatric species of echimyid rodents, Proechimys semispinosus and Hoplomys gymnurus, in Central Panama. Issue 1 (2nd January 2017) - Dupre, S.I.; Lambert, T.D.; Adler, G.H.; Hegde, L.M.; Kennedy, E.H.
Abstract : An understanding of the mechanisms that allow ecologically similar species to coexist is critical in making effective conservation and restoration decisions. This understanding is especially important when considering species that play critical roles in forest regeneration. Small mammals influence Neotropical forest regeneration following disturbance through their actions as seed dispersers and seed predators. In Panama, the Central American spiny rat ( Proechimys semispinosus ) and the armored rat ( Hoplomys gymnurus ) persist sympatrically despite a similar diet and seasonal food resource limitation. To study the relationship between these species, we conducted behavioral arena trials to analyze interspecific and intraspecific interactions. Our goal was to determine whether behavioral dominance between H. gymnurus and P. semispinosus exists, potentially reducing the intensity of aggressive competition and allowing the two species to coexist sympatrically. Aggression data were analyzed using a zero-inflated negative binomial regression model showing that species pairing was a significant predictor of aggression, supporting the existence of behavioral dominance by P. semispinosus over H. gymnurus . Investigative behavior data were analyzed using the Kruskal–Wallis test and showed a significantly higher level of investigative behavior for P. semispinosus towards H. gymnurus during the dry season when resources are scarce compared to the wet season when resources are plentiful.